Nasaan ang pistan - Perez, Rudy Ocampo
A discussion exploring the value people attach to feasts, probing the necessity of expensive celebrations, the choice of dates to celebrate and the overall relevance of feasts. It aims to show the need to return to the real meaning and the value of fiestas.